The Main Bioactive Constituents of Traditional Kurdish Plant Achellia oligocephala DC.; their Antiproliferative and Antioxidant Activities. - Hawraz Ibrahim M. Amin (Zanco Journal of Pure and Applied Sciences, 2020)
Achellia oligocephala DC. , which grows in the mountains, is very popular as wound healing and gastrointestinal complaints. This research article reports the first study of the phytochemical investigation and biological properties of bioactive secondary metabolites from the traditional Kurdish plant Achellia oligocephala. (+) - Luteolin-6-C-glucoside (AO1) and Lupeol (AO2) were isolated from aerial parts for the first time from this plant. The antiproliferative activity was measured against three human tumour cell lines, MCF7, SkBr3, and BG-1 cancer cells by using the MTT assay. Notably, the (+) - Luteolin-6-C-glucoside showed significant antiproliferative activity against MCF7 cancer cell line, IC50 value (10 µg/mL). The antioxidant activity of AO1 and AO2 were evaluated on total antioxidant capacity (TOAC) test. Interestingly, its showed a remarkable antioxidant activity compared to standard antioxidant. This study confirms that (+) - Luteolin-6-C-glucoside can be considered a natural anticancer and antioxidant compound.